The Influence Of Mobile Marketing, Integrated Digital Marketing And Push Digital Marketing On Buying Interest Of Muslim Consumers Instagram Koyu Hijab Followers - Bianca Shopa Ul Muntajah Bian (IAIN Langsa, 2022)
The digital revolution happening nowadays brings significant impacts. Therefore, internet creates a new opportunity for the entrepreneurships, product providers, and the ease of unlimited transaction. The implementation of digital marketing has targeted Muslim fashion product. There are Syariah Economic Report data from quartal of 2019-2020 indicating the decrease due to pandemic of Covid-19, although the Koyu Hijab experienced product sale increase. This research aims at finding out the influence of mobile marketing, integrated digital marketing, and push digital marketing towards the Muslim consumers’ interest. The type of research implemented was descriptive quantitative utilizing primary data. The data collection was done using questionnaire with 4 Liker scales. The sampling technique used was purposive sample method covering 400 respondents. The data analysis technique used was multiple linear regression, coefficient determination test, t-test, and f-test. The analysis instrument applied in the research was IBM statistic version 2.1. The research result shows that mobile marketing, integrated digital marketing, and push digital marketing has positive and significant influence simultaneously towards Muslim consumers’ interest variable. Keywords: Mobile Marketing, Integrated Digital Marketing, Push Digital Marketing, Muslim Consumers’ Interes